Rival Capitalists : International Competitiveness in the United States, Japan, and Western Europe - Hart, Jeffrey (Ithaca, NY : Cornell University Press, 2018)
Great Britain, France, Germany, and Japan. Surveying the development of the steel, automobile, and semiconductor industries in each of these countries, Jeffrey A. Hart illuminates the role of national policy in a changing world.Hart describes the global structure of production and consumption in the five major capitalist countries and offers a rich comparative history of their industrial policymaking. He concludes that variations in statesocietal arrangements--and the impact these differences have on the creation and diffusion of new technologies--provide the best explanation for divergences in international competitiveness. In Japan, state and business are allied, but labor is marginalized, whereas in Germany, labor and business are allied, and the state is decentralized. Yet both countries have become increasingly competitive because they have developed institutional mechanisms for technology diffusion. France's state-led system, in contrast, is linked with only moderate competitiveness. The decline of competitiveness in the United States and Britain, Hart concludes, may be attributed to state-societal arrangements that have allowed one actor-labor in Britain, business in the United States-to dominate policymaking.Rival Capitalists will be an invaluable source for policymakers and business analysts as well as scholars and students of political economy, international relations, industrial organization, industrial sociology, and comparative politics.
Frontmatter -- Contents -- Figures and Tables -- Preface -- 1. State-Societal Arrangements and International Competitiveness -- 2. Japan -- 3. France -- 4. The United Kingdom -- 5. Germany -- 6. The United States -- 7. Conclusions -- Glossary -- Abbreviations -- Index
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 19. Feb 2019).
Includes bibliographical references and index.
JSTOR
Keywords: Competition, International; Industrial policy -- European Economic Community countries; Industrial policy -- Japan; Industrial policy -- United States; Industries -- United States; Industries -- Japan; Concurrence internationale; Industrie -- États-Unis.; Industrie -- Japon; Industrie -- Pays de l'Union européenne.; Politique industrielle -- États-Unis.; Politique industrielle -- Japon; Politique industrielle -- Pays de l'Union européenne.; POLITICAL SCIENCE / Political Economy; Industries; Competition, International; Industrial policy; European Economic Community countries; Japan; United States; Internationale Wettbewerbsfähigkeit; Internationaler Vergleich; Westeuropa; Japan; USA; Concurrentie; Economische politiek; Geschichte 1960-1989.